Tendency of Internet Addiction in College Students (Case Study on Public Administration Students of the Faculty of Social and Political Sciences, HKBP Nommensen University) - Degodona, Laurencia Primawati; Rajagukguk, Jonson; Zebua, Jul Forman; Br Sihaloho, Juli Tiarma; Sihura, Risky Roi Putra (Department of Geography Education, Faculty of Social Sciences, Universitas Negeri Medan, 2024)
The internet provides tremendous educational benefits for students and also provides better communication, information, and social interaction opportunities for young people, but excessive internet use can lead to negative psychological addiction. This study aims to quantitatively describe the tendency of internet addiction in the population of students majoring in Public Administration from the class of 2020, 2021, and 2022. The total sample taken was 142 people, including all students from the three batches. The data analysis method applied in this research is the crosstab or cross tabulation analysis technique. The data analysis process involved the use of SPSS V.25 statistical software. From the results of the analysis of gender and range of addiction, it can be seen that the majority of respondents, both males (66.7%) and females (69.9%), experience a moderate level of internet addiction, especially social media. The number of respondents who experienced moderate addiction reached 98 out of a total of 142 respondents. In the analysis of respondents' age groups and range of addiction, it can be seen that three age groups dominate, namely 19, 20 and 21 years old. Of the 28 respondents aged 19, 17 of them experienced moderate addiction. In the 20-year-old age group, out of 43 respondents, 33 were classified as moderately addicted. While in the 21-year-old age group, out of 37 respondents, 26 of them also showed a moderate level of addiction. Furthermore, the tendency of internet addiction in college students is dominated by two main aspects: characteristics and excessive use. Students who feel attached to the internet tend to always think about and find it difficult to control their use. Keywords: Tendency; Addiction; Internet; College Students